A blue-emitting Eu2+-activated BaZnAl10O17 phosphor for white light emitting diodes: structure and luminescence properties. Issue 24 (26th October 2022) - Zhang, Tianqing; Jiang, Xiliang; Chen, Rujia; Liu, Bingyan; Yang, Weiling; Li, Ce; Lin, Hai; Liu, Huisheng; Li, Chun; Zeng, Fanming; Su, Zhongmin
Abstract : In the process of developing high-performance LCDs, narrow-band emitting phosphors with excellent performance are indispensable. Abstract : In the process of developing high-performance LCDs, narrow-band emitting phosphors with excellent performance are indispensable. In this study, a narrow-band blue phosphor BaZnAl10 O17 :Eu 2+ with an emission peak at 433 nm (which can be excited by near-ultraviolet light) and a full width at half maximum of 46 nm was found. The synthesized BaZnAl10 O17 :Eu 2+ phosphor exhibits low thermal quenching behavior. There is only 16.4% loss in emission intensity at 423 K compared to the initial intensity at room temperature. Using the narrow-band emission phosphor BaZnAl10 O17 :Eu 2+ as the blue light source, the prepared white LED device excited using a near-ultraviolet chip emits high-brightness white light (CCT = 4436 K, R a = 93.96), whose CIE coordinates are (0.3387, 0.3785) and CG can reach 99% of the NTSC standard. The narrow-band blue-emitting BaZnAl10 O17 :Eu 2+ phosphor has potential application value in white light-emitting diodes.